La sabiduría multiforme y nuliforme en San Buenaventura - Barrajón, L.C., Pedro (Alpha Omega, 2018)
Summary: The author had presented in a previous article the two first branches of christian wisdom («sapientia uniformis» and Csapientia omniformis») (Cf. «AlphaOmega» 2 (1999) 13-48), according to St. Bonaventure’s exposition in his final work «Collationes in Hexaemeron». He now dedicates this study to analyse the other two: «sapientia multiformis» and «sapientia nulliformis». The former is the wisdom of Holy Scripture. The latter is the wisdom of mystical experience. Through «sapientia multiformis» Saint Bonaventure describes theology, in which he combines his peculiar vision of history, based on Augustinian tradition, with that of Joachim da Fiore, the Calabrian abbot, who had foreseen the coming of a new age of the Spirit. Bonaventure tries to balance Joachim’s extreme position with a more moderate one. He can do so, thanks to his Christ-centred view of theology and history. In «sapientia nulliformis», Bonaventure places the mystical experience of contemplatives, men and women who already belong to the new era of Christified persons, who are completely absorbed in God’s Presence, like Saint Francis of Assisi.